Disruption of transverse‐tubular network reduces energy efficiency in cardiac muscle contraction. (16th August 2020) - Mellor, Nicholas G.; Pham, Toan; Tran, Kenneth; Loiselle, Denis S.; Ward, Marie‐Louise; Taberner, Andrew J.; Crossman, David J.; Han, June‐Chiew
Abstract: Aim: Altered organization of the transverse‐tubular network is an early pathological event occurring even prior to the onset of heart failure. Such t‐tubular remodelling disturbs the synchrony and signalling between membranous and intracellular ion channels, exchangers, receptors and ATPases essential in the dynamics of excitation‐contraction coupling, leading to ionic abnormality and mechanical dysfunction in heart disease progression. In this study, we investigated whether a disrupted t‐tubular network has a direct effect on cardiac mechano‐energetics. Our aim was to understand the fundamental link between t‐tubular remodelling and impaired energy metabolism, both of which are characteristics of heart failure. We thus studied healthy tissue preparations in which cellular processes are not altered by any disease event. Methods: We exploited the "formamide‐detubulation" technique to acutely disrupt the t‐tubular network in rat left‐ventricular trabeculae. We assessed the energy utilization by cellular Ca 2+ cycling and by crossbridge cycling, and quantified the change of energy efficiency following detubulation. For these measurements, trabeculae were mounted in a microcalorimeter where force and heat output were simultaneously measured. Results: Following structural disorganization from detubulation, muscle heat output associated with Ca 2+ cycling was reduced, indicating impaired intracellular Ca 2+ homeostasis. This led to reduced force production and heat output by crossbridge cycling. The reduction in force‐length work was not paralleled by proportionate reduction in the heat output and, as such, energy efficiency was reduced. Conclusions: These results reveal the direct energetic consequences of disrupted t‐tubular network, linking the energy disturbance and the t‐tubular remodelling typically observed in heart failure.